PWE-120 What Do Healthcare Professionals Know About Fatigue In Patients With Ibd And How Do They Manage It?. (9th June 2014) - Czuber-Dochan, WJ; Norton, C; Berliner, S; Bredin, F; Darvell, M; Forbes, A; Gay, M; Nathan, I; Ream, E; Terry, H
Abstract : Introduction: Fatigue is one of the top complaints in inflammatory bowel disease (IBD) with 40% of patients in remission and 86% in active condition reporting fatigue. 1 However patients report that their complaints of fatigue are often not addressed in clinical consultations. 2 This study aimed to gain an understanding of healthcare practitioners' (HCPs) perception of IBD fatigue as experienced by people with IBD. Methods: Descriptive phenomenology with purposive sampling was used to identify a range of professionals (gastroenterologists, IBD nurses, general practitioners, dietitians, psychologists and pharmacists). In-depth semi-structured interviews were conducted with 20 HCPs who work with people with IBD (June–Dec 2012). Colazzi's framework was used to analyse the data. 3 Results: Three main themes and several sub-themes were identified. The main themes were: the phenomenon of fatigue as perceived by HCPs; the impact of fatigue on patients' lives; and the methods used by HCPs to deal with fatigue. Fatigue was identified as an important, but difficult and often frustrating, symptom to understand. The study participants perceived fatigue as 'a complicated and complex thing'. HCPs reported that fatigue impacts on the emotional, private and public aspects of patients' functioning, however there were very few methods suggested on how to assess and manage the fatigue in a systematic way. Many expressed a desire for better education about fatigue and better multi-disciplinary effort to manage fatigue. Conclusion: Despite fatigue being one of the symptoms most frequently reported by IBD patients, it remains poorly understood by HCPs, who find fatigue challenging and frustrating. There is a need for a systematic and structured assessment and management of this distressing symptom and HCPs should communicate with each other about care for each individual patient. There is a need for an assessment framework and for intervention strategies to be tested. It is essential for multidisciplinary team members to be involved in planning and managing coordinated care of patients reporting fatigue in IBD. References: Czuber-Dochan W, Ream E, Norton C, Review article: description and management of fatigue in inflammatory bowel disease. Alim Pharma and Therap 2013;37(5):505–16 Czuber-Dochan W, et al. The experience of fatigue in people with inflammatory bowel disease: an exploratory study. JAN 2013;69(9):1987–99 Colazzi P, Psychological research as a phenomenology views it. In Valle R, King M Eds. Existential Phenomenological Alternatives for Psychology . 1978;New York: New York University Press Disclosure of Interest: W. Czuber-Dochan Grant/research support from: Big Lottery Fund managed by Crohn's and Colitis UK, C. Norton Grant/research support from: Big Lottery Fund managed by Crohn's and Colitis UK, S. Berliner Conflict with: Trustee Crohn's and Colitis UK, F. Bredin Grant/research support from: Big Lottery Fund managed by Crohn's and Colitis UK, M. Darvell Employee of: Crohn's and Colitis UK, A. Forbes Grant/research support from: Big Lottery Fund managed by Crohn's and Colitis UK, M. Gay Conflict with: Vice-Chair and Trustee Crohn's and Colitis UK, I. Nathan Grant/research support from: Big Lottery Fund managed by Crohn's and Colitis UK, E. Ream: None Declared, H. Terry Employee of: Crohn's and Colitis UK.